Unsafe Occupational Health Behaviors: Understanding Mercury-Related Environmental Health Risks to Artisanal Gold Miners in Ghana - Armah, Frederick A.; Boamah, Sheila A.; Quansah, Reginald; Obiri, Samuel; Luginaah, Isaac (Frontiers in Environmental Science, 2016)
The relationship between environmental exposure and health outcomes is complex, multidirectional and dynamic. Therefore, we need an understanding of these linkages for effective health risk communication. Despite the severe health hazards, artisanal gold mining is widespread globally, with an estimated 30 million people engaged in it. In this study, the relationships between artisanal gold miners’ knowledge of environmental and health effects of Hg and compositional, contextual and occupational factors were assessed using generalized linear models (negative log-log regression). A cross-sectional survey in three urban gold mining hubs in Ghana (Prestea, Tarkwa and Damang), was carried out among 588 (482 male and 106 female) artisanal gold miners. The results showed that 89% of artisanal gold miners had very low to low levels of knowledge whereas 11% had moderate to very high levels of knowledge of deleterious health effects of Hg. Also, individuals who perceived their health-related work conditions to be excellent had very low to low levels of knowledge of environmental and health effects of Hg. Interestingly, artisanal gold miners who were still working were less likely to know the environmental and health effects of Hg compared with their counterparts who were currently unemployed. Similarly, artisanal gold miners who had attained either primary or secondary education were less likely to know the environmental and health effects of Hg compared with their counterparts who had no formal education. This finding, although counterintuitive, can be understood within the fact that artisanal gold miners in Ghana without formal education tend to have considerably higher number of years of practical experience compared with their counterparts with formal education. Female artisanal gold miners were 68% less likely to know the environmental and health effects of Hg compared with their male counterparts (OR=0.32, p<0.05). Artisanal gold miners who had previously encountered occupational health problems were significantly more likely to know the environmental and health effects of Hg compared with their counterparts without any previous occupational health problems (OR=4.86, p<0.0001). Although artisanal gold miners who are 25-34 years old were more likely to know than their counterparts who are 18-24 years old, there were no differences in knowledge